Quantum spin transistor with a Heisenberg spin chain - O. V. Marchukov; A. G. Volosniev; M. Valiente; D. Petrosyan; N. T. Zinner (Nature Communications, 2016)
Systems of interacting quantum spins provide a basis for quantum computation devices. Here, the authors demonstrate a quantum spin transistor in a Heisenberg spin chain, which may be realized in a system of trapped cold atoms.